Developing an Enhanced Virtual Reality Simulation Capability for the Coal Mining Industry - Stothard, Phillip (UNSW School of Mining, 2008)
The CSPL Project “Developing an Enhanced Virtual Reality Simulation Capability for the Coal Mining Industry” was proposed in 2005 as a three-year project concerned with the continued development and implementation of an enhanced capability in virtual reality (VR) simulation for improving OH&S management and performance in the Australian Coal Mining Sector. CSPL had developed and implemented proof of concept simulations prior to commencement of the project based on ‘off the shelf’ PC technology as identified by Stothard et al (2001).Under the earlier projects, a core capability in VR simulation had been established and was clearly demonstrated. This capability provided a foundation for developing and expanding the project to a more advanced suite of simulations. However, the technology from the previous project required updating to take advantage of the rapidly changing simulation technology and to make the simulations more realistic and meaningful. From the outset of this project, the aim was to enhance at least two of the existing simulations and develop several new simulations in line with the findings and recommendations of Stothard and Galvin(2005) where the researchers concluded that simulation technology had advanced significantly since theoriginal Scoping Study of Stothard et al (2001) and that high powered, cost effective technology, was available to simulate complex mining simulations associated with coal mining. The enhanced VR project proposed that two of the original modules – Rib and Roof Stability and Unaided Self Escape should be enhanced because they offered important OH&S benefits and because they offered a platform on which to base new simulations. It was envisaged that 80% of the equipment and models already built and deployed at Newcastle Mines Rescue Station (NMRS) and the School of Mining Engineering at UNSW (UNSW) could be migrated to the advanced system. The project had a total budget of $1715600 over three years with a later commercial component of$250000 to produce more content. Core project aims were to, Build and maintain an internal module building capability, Use off the shelf software and hardware, Produce photo-realistic simulations Have in place a sustainable commercial footing for the long term development of immersive, interactive simulations at the end of the project (or be very close to achieving this).The benefits of VR simulation are described in earlier VR simulation projects funded by Coal Services that have demonstrated that immersive, interactive VR simulations provide for more effective education, training and assessment in OH&S (Fowler et al 2005).The project aims were to immerse trainees in a multitude of realistic mining environments and engage the trainees during the simulation session. The interaction with the simulations and the ‘scenarios’ would be drawn from the core competencies for mine workers. This report reviews the progress made during the three year project and presents data acquired during that period and also a business case for the continuation of the project longer term